Surgical Tactics for Intestinal Duplication Cyste Causing Intestinal Invagination (Case From Practice) - Sabirov, Ruslan (Asian Pacific Journal of Environment and Cancer, 2021)
We give a case study of how we encountered a very rare pathology - an intestinal duplication cyst of the terminal ileum, which manifested itself very early in a child of two months with a complication of invaginal intestinal obstruction. Taking the very serious condition of the newborn into consideration, the tactics of minimally invasive surgery were used - mini laporatomy, intestinal disinvagination, excision of enterocysts, and the application of cecostomy. Combined anesthesia: Total intravenous anesthesia (sibazon + ketamine) with the preservation of spontaneous breathing + spinal anesthesia with bupivacaine 1.0 ml at the level of Th 11. This managed to avoid a more traumatic abdominal operation, thereby not only saving life, but also preventing various possible complications.